2017
DOI: 10.1186/s12905-017-0404-0
|View full text |Cite
|
Sign up to set email alerts
|

Case report: term birth after fertility-sparing treatments for stage IB1 small cell neuroendocrine carcinoma of the cervix

Abstract: BackgroundAdvances in cervical cancer management for childbearing women have led to less radical approaches. Use of fertility-sparing treatment to treat small cell neuroendocrine carcinoma (SCNEC) is challenging owing to the aggressive nature of the disease, even in early stage disease.Case presentationA 25-year-old nulligravida woman presented with malodorous vaginal discharge and was diagnosed to have an exophytic cervical SCNEC. A magnetic resonance image scan showed no evidence of parametrial invasion or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This data is consistent with other improved outcomes after removal of uterine septum resection 6 . Most data regarding pregnancy outcomes with a neocervix or no cervix after trachelectomy come from fertility sparing procedures for early stage cervical cancer or case reports 7,8 . Of 436 reported cases of pregnancy after fertility sparing surgery nearly 67% resulted in live birth, 26% were preterm and 10% had a second trimester spontaneous abortion – twice as high as the general population 9 .…”
Section: Discussionsupporting
confidence: 76%
“…This data is consistent with other improved outcomes after removal of uterine septum resection 6 . Most data regarding pregnancy outcomes with a neocervix or no cervix after trachelectomy come from fertility sparing procedures for early stage cervical cancer or case reports 7,8 . Of 436 reported cases of pregnancy after fertility sparing surgery nearly 67% resulted in live birth, 26% were preterm and 10% had a second trimester spontaneous abortion – twice as high as the general population 9 .…”
Section: Discussionsupporting
confidence: 76%
“…Montoya-Williams et al believed that some VBAC parturients have a prolonged labor process due to insufficient uterine contraction intensity, while the use of oxytocin can effectively enhance uterine contraction and productivity, and speed up the process of vaginal delivery. Some scholars have confirmed that the use of high-dose oxytocin is related to the risk of uterine rupture [ 7 ]. Although it is obvious that pregnant women can inject oxytocin intravenously during VBAC delivery, ACOG does not show the dose limit of oxytocin during uterine rupture and vaginal trial delivery [ 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…Nine patients were dead of disease within 4 years of diagnosis. The longest survivor was for 84 months [4]. The poorest outcome was of woman who died one month after diagnosis as stage IV-B [17].…”
Section: Discussionmentioning
confidence: 99%